The experience of diagnostic radiography students during the early stages of the COVID‐19 pandemic – a cross‐sectional study. Issue 4 (4th September 2021) - Lawson Jones, Gaynor; York, Helen; Lawal, Olanrewaju; Cherrill, Richard; Mercer, Sarah; McCarthy, Zoe
Abstract: Introduction: The rationale for this study was to ascertain the impact of the COVID‐19 pandemic on Undergraduate B.Sc (Hons) Diagnostic Radiography students at the University of Hertfordshire in the UK. This would provide an ideal opportunity for students to reflect on their experience and indicate if they required additional support from the University. Methods: An online anonymous cross‐sectional survey was deployed to all year groups ( n  = 283) during the first nationwide lockdown in May 2020, eliciting qualitative responses on questions about the effect of the pandemic; emotions experienced; support required and consideration of their choice of a career in the health sector. Results: Two hundred and one students responded to the survey, with many having experienced the illness or loss of a loved one. Trying to balance family commitments and study was a concern to some students, as well as struggling with the financial burden of job losses or furlough. Many students commented that educational support was a requirement with the move to online teaching and assessment. The main focus of student responses was the emotions that they had experienced, many of which were negative. Anxiety and fear were commonly expressed feelings, along with sadness and feelings of isolation. A small number of students reported feeling grateful, happy and relieved. An overwhelming majority of respondents commented that they were proud to be healthcare students and they were resolute in wanting to continue the course and join the frontline of the NHS workforce. Conclusion: Some students have been deeply affected by their experiences of the pandemic, and University support mechanisms should be refined to better assist with their ongoing challenges. Abstract : United Kingdom‐based students surveyed regarding their emotions during the first phase of the Covid‐19 pandemic. Particular note was made of their intended career in healthcare and if their decisions had altered.